2018
DOI: 10.1161/hypertensionaha.117.10496
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Initial Injury Severity and Posttraumatic Stress Disorder Diagnoses With Long-Term Hypertension Risk After Combat Injury

Abstract: The associations between injury severity, posttraumatic stress disorder (PTSD), and development of chronic diseases, such as hypertension, among military service members are not understood. We sought to (1) estimate the prevalence and incidence of PTSD within a severely injured military cohort, (2) assess the association between the presence and chronicity of PTSD and hypertension, and (3) determine whether or not initial injury severity score and PTSD are independent risk factors for hypertension. Administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 39 publications
3
47
4
1
Order By: Relevance
“…Our prior work on this topic has suggested that PTSD and injury severity are independent risk factors for the subsequent development of HTN. 15 However, the present study suggests that may only be true for more severely injured patients.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our prior work on this topic has suggested that PTSD and injury severity are independent risk factors for the subsequent development of HTN. 15 However, the present study suggests that may only be true for more severely injured patients.…”
Section: Discussionmentioning
confidence: 52%
“…[9][10][11][12] However, these associations are complicated by the high prevalence of psychiatric morbidity in critically ill patients, 13,14 which has in turn been correlated with poor longterm outcomes such as cardiovascular disease. 15 The primary limitation of the literature so far is selection bias: patients who become acutely ill are fundamentally different from those that do not. From this lens, combat casualties are a particularly interesting group to study.…”
Section: Introductionmentioning
confidence: 99%
“…For example, military service puts individuals at increased risk of traumatic injury, which has been shown to be associated with higher risk of subsequent CVD 11 and hypertension. 11,20 Increased mental health diagnoses, including depression, anxiety 21 and posttraumatic stress disorder 20,22 within military veterans has also been linked to subsequent CVD risk. Higher prevalence of obesity 23 and smoking behavior 24 have also been linked to higher risk of CVD in military veterans.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is a major modifiable CVD risk factor and a promising intermediary mechanism by which trauma and PTSD may influence CVD risk (Benjamin et al ., 2018). Both trauma and PTSD have been linked to increased hypertension risk across cross-sectional (Cohen et al ., 2009; Granado et al ., 2009; Riley et al ., 2010; Glaesmer et al ., 2011; Pietrzak et al ., 2011; Stein et al ., 2014) and longitudinal studies (Sumner et al ., 2016; Howard et al ., 2018). Additional studies have indicated that individuals with trauma and sub-clinical PTSD symptoms also have elevated hypertension risk compared to individuals without trauma (Pietrzak et al ., 2011; Sumner et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%